A REVIEW OF COMPUTATIONAL FLUID DYNAMICS (CFD) APPROACHES FOR THERMAL ANALYSIS AND OPTIMIZATION - Hussain, Dr. Abid (Journal of Global Research in Mathematical Archives(JGRMA), 2025)
Numerous scientific and technological applications, including differential equations, combustion, aircraft, autos, refrigeration, propulsion, heat exchangers, & nuclear engineering, depend heavily on the coupling of heat transfer with fluid flow. Computational fluid dynamics (CFD) has been effectively applied over the years to address a variety of conjugate heat transfer and fluid flow issues using computers. The article provides an in-depth discussion of thermal and cooling methods based on advanced Computational Fluid Dynamics (CFD) technologies in engineering. The analysis of key CFD techniques—i.e., conjugate heat transfer, radiation-convection modeling, and multiphase phase-change processes—aims to achieve precise simulation of coupled thermal phenomena. Various methods, including Design of Experiments (DOE), Response Surface Methodology (RSM), domain decomposition, and AI-enabled approaches, are applied to CFD to enhance computational efficiency. Practical applications in biomedical, mechanical, and missile engineering demonstrate the role of CFD in predicting performance, reducing costs, and improving designs. A thorough literature review also helps identify the current trends and challenges in CFD-based thermal analysis. The study presents an intelligent and efficient integrated framework for the CFD-driven thermal system design.